(untitled) (AYUSHDHARA, 2016)
Menorrhagia is a very common complaint among females in recent years. The World Health Organization reports that 18 million women aged 30-55 years perceive their menstrual bleeding to be exorbitant. Reports show that only 10% of these women experience blood loss severe enough to cause anaemia or be clinically defined as menorrhagia. Asrgdara means heavy vaginal bleeding during or before or after menstrual period. Though the menorrhagia is not directly described in any textbook of Ayurveda but it is quite similar to Asrgdara having uterine bleeding other than menstrual bleeding among other causes. Menorrhagia is not new for Ayurveda which is described under the heading of the Asrgdara. The main clinical feature of both menorrhagia and Asrgdara is uterine bleeding along with its other complications. The main types of Asrgdara are Vataja, Pittaj, Kaphaj, and Sannipataj Trividhpariksha also helps to diagnose the disease by means of Darshan (inspection), Sparshan (palpitation) and Prashan (questioning). There are so many generic and patent drug available in Ayurveda like Raktapradarharyog, Ashokaristha, Pradarantakras, Pradrariras may helpful to stop the bleeding and also able to cure the complications of Asrgdara..Thus Ayurvedic treatment may have strong ability of breaking down the pathogenesis of Asrgdara and its management also.